臺灣課程改革理論基礎再思Revisiting the Theoretical Bases of Taiwan's Curriculum Reform - 黃顯華Hin-Wah Wong; 徐慧璇Hui-Xuan Xu (Higher Education Foundation, 2006)
教育工作者如何理解「課程」此一概念，對課程改革中的課程設計、課程決定模式、課程實施、課程評價／研究均有重要啟示。本文即從這些維度，針對教育部在二十世紀一九九○年代頒布課程標準與課程綱要的文本與相關研究進行比較分析。 結果發現：課程標準傾向於將課程定義爲「學科」，其改革過程可分為發 展、傳遞、採用三個階段；課程綱要傾向於將課程定義爲「經驗」，其改革表現出持續發展的傾向。但後者在課程決定、實施及研究取向上仍保留課程定義爲「學科」時的部分特徵。從課程的定義角度觀之，臺灣課程改革的性質正從課程作爲「科目」的方向朝課程作爲「經驗」的方向發展。 The way educators understand the concept of curriculum has significant implication to the nature of curriculum design, decision, implementation, evaluation and research in curriculum reform. Based on these dimensions, this article compares documents and research reports of curriculum standard of 1993 with those of curriculum program of 1998. It comes to the conclusion that curriculum standard tends to define curriculum as an academic discipline, in which reform is a repeated process of development, diffusion and adoption. Curriculum program tends to define curriculum as an experience, in which reform is a continuous development process. However, the latter has inherited some characteristics of the former in curriculum decision, implementation and research. From the perspective of the definition of curriculum, the nature of curriculum reform in Taiwan can be considered as moving from "academic discipline" to "experience".